(untitled) (Journal of the College of Education for Women, 2023)
Edward Albee (1928-2016) is an American dramatist who is notorious for his controversial works. Albee’s plays generate a crisis of a restraint situation and a point of no return where characters trespass the limits and get caught up in a tragic cycle. The Goat or Who is Sylvia? )2000) is one of his controversial pieces, addressing (human-animal relations). This theatrical masterpiece unleashes man’s wildest desires and ravaging behavior. Bestiality is a criminal offense placed in the domain of mental disorders attributed to the lack of emotional support, anxiety, depression, and psychological problems. It is also a serious moral infraction of communities’ socio-religious traditions. In this play, Martin’s bestiality leads to the collapse of his marriage and the slaughter of his goat. Thus, this paper intends to address bestiality in the light of queer theory. Furthermore, this study aims to comprehend the intricacies of human behaviour, the relationship between humans and animals, and its social and psychological effects on family members.